Learning or grading: an ethical dilemma in medical students - Bustos Saldaña, Rafael (Acta Bioethica, 2022)
Medical students must shape their future work, before, during and after their student life. It is a necessity for physicians in general from their student stage to have an apprenticeship based on what they must perform for their later professional work activity. This school development of learning is usually influenced by the form of the curricula that each of the educational institutions allow. In most of them, the privileges that students have during their trajectory are granted through the grade point averages they have in each school cycle. Very often, achieving the privileges offered by schools creates bioethical problems for students who have professional learning as an alternative. The confrontation of this dilemma can cause alterations in the student’s school development and even in his physical or mental health.